2021
DOI: 10.21083/partnership.v16i1.6462
|View full text |Cite
|
Sign up to set email alerts
|

Data in the Time of COVID-19: How Data Library Professionals Helped Combat the Pandemic

Abstract: As the world struggled to respond to the COVID-19 pandemic, researchers worked around the clock to understand what was going on, medically, socially, and economically. At the same time, usual research processes were disrupted: campuses were closed and normal government data collection and dissemination went haywire. Data professionals in academic libraries sprang into action to help. They shared resources, developed workshops, helped find alternative methods of carrying out research, and found ways of coping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They shared resources, developed workshops, helped find alternative methods of carrying out research, and found ways of coping with the influx of Covid-related data.' 9 Generally speaking, RDM is supported by digital infrastructures of varying sophistication, from standard hard drives to integrated cloud solutions. 10 The FAIR (Findability, Accessibility, Interoperability and Reusability) data principles have been increasingly acting as a useful focal point to assess the maturity of research data infrastructures and have been recently described as a tool to help build campus infrastructure and change culture.…”
Section: Introductionmentioning
confidence: 99%
“…They shared resources, developed workshops, helped find alternative methods of carrying out research, and found ways of coping with the influx of Covid-related data.' 9 Generally speaking, RDM is supported by digital infrastructures of varying sophistication, from standard hard drives to integrated cloud solutions. 10 The FAIR (Findability, Accessibility, Interoperability and Reusability) data principles have been increasingly acting as a useful focal point to assess the maturity of research data infrastructures and have been recently described as a tool to help build campus infrastructure and change culture.…”
Section: Introductionmentioning
confidence: 99%